I know that the identity $$ s_\mu = \sum_{\mu-\lambda \text{ is a horizontal strip}} \;\sum_{\alpha\vdash|\lambda|} \frac{\chi^\lambda_\alpha}{z_\alpha} \prod_i(p_i-1)^{a_i} $$ holds. Here $\alpha=1^{a_1}2^{a_2}\dotsb$ in exponential notation; in other words, $a_i$ is the number of times that $i$ occurs in $\alpha$.

I know this because I can show that it is essentially equivalent to the formula I.5 of Garsia and Goupil EJC 2009.

Note that the equality of top-degree terms is the well-known expansion of a Schur function in terms of power sum symmetric functions, so it suffices to show that all lower degree terms vanish.

I feel that his simple-looking formula should have a direct and elegant proof. Is there one?


I would like to suggest an interpretation using super symmetric functions. These are symmetric functions that are symmetric in two sets of variables $\{x_i\}$ and $\{y_j\}$ separately. They satisfy the property that setting a single $x_i$ variable to equal $z$ and a single $y_j$ variable equal to $z$ gives a polynomial independent of $z$, in addition to several other conditions (see Chapter 1, Section 3, Exercise 23 of Macdonald's book). Note that since it's independent of $z$, it's the same as just setting $x_i = y_j = 0$, which amounts to considering the same super symmetric function in a smaller set of variables.

A concrete description of supersymmetric functions is as follows. The supersymmetric functions are the image of the map $\Lambda \to \Lambda \otimes \Lambda$ given by $(\mathrm{Id} \otimes S) \circ \Delta$, where $\Lambda$ is the ring of symmetric functions, $\Delta$ is the usual comultiplication, and $S$ is the usual antipode (which sends the power sum $p_i(y)$ to $-p_i(y)$). The variables in the second factor (i.e. $\{y_j\}$) are the "super variables". Because the map is injective, the supersymmetric functions are abstractly isomorphic to $\Lambda$, but they are convenient for performing certain specialisation tricks. But let me give an example: $$ \sum_{r=0}^\infty e_r(x/y) t^r = \frac{\prod_i(1+x_i t)}{\prod_j (1+y_j t)}. $$ These are the elementary super symmetric functions. You can see that if you set a single $x_i = z$ and a single $y_j = z$, then a factor of $1+zt$ cancels in the numerator and denominator, giving an expression independent of $z$ as stated above. Another example is that $p_i(x/y) = p_i(x) - p_i(y)$.

Now we're in a situation where we can explain the identity. Clearly $s_{\mu}(x) = s_\mu(x,1/1)$ by the specialisation property of super symmetric functions. But the right hand side can be obtained by first setting an $x_i$ equal to 1, then passing from $\Lambda$ to super symmetric functions, then setting a $y_j=1$ and all other $y$'s to zero (that setting $x_i=1$ commutes with passing to super symmetric functions isn't totally obvious, but I'm omitting it for the sake of brevity). The upshot of this is that $s_\mu(x,1) = \sum_\lambda s_\lambda(x) s_{\mu/\lambda}(1)$, and $s_{\mu/\lambda}(1)$ is zero unless $\mu/\lambda$ is a horizontal strip. This gives the outer sum in your expression. Then we recognise that second part of the operation replaces $p_i(x)$ with $p_i(x/1) = p_i(x) - p_i(1) = p_i(x)-1$, which recovers your expression, where I have taken for granted that $$ s_\lambda(x) = \sum_{\alpha \vdash |\lambda|} \frac{\chi_\alpha^\lambda}{z_\alpha}\prod_i p_i^{a_i}. $$

  • $\begingroup$ I'm not sure if I'm allowed to follow-up your answer with a question. In any case what happens if you apply your supersymmetric construction in the case when $\Lambda$ is the tensor algebra $T(V)$ (viewed as a Hopf algebra)? $\endgroup$ Nov 15 '20 at 17:58
  • $\begingroup$ I don't know how to interpret the "super" tensor algebra when defined with the Hopf structure analogously to above. A more analogous construction seems to be to consider the map $T(V) \to T(V\oplus V)$ induced by $v\mapsto (v,-v)$. (Note that $T(V\oplus V) \neq T(V)\otimes T(V)$.) The image of an element of $T(V)$ under this map has the property that if you set the element corresponding to $(e_i,0)$ equal to the element corresponding to $(0,e_i)$, the output is independent of the actual value. (This is like the cancellation above, but you must use the same index variable and super variable.) $\endgroup$ Nov 15 '20 at 23:37

Here is another argument. Let $\chi^{\mu/k}$ denote the skew character of the symmetric group $\mathfrak{S}_n$ corresponding to the skew shape $\mu/k$. Then by Pieri's rule, $$ \sum_{\mu-\lambda\ \mathrm{is\ a\ horizontal\ strip}} \sum_{\alpha\vdash|\lambda|}\frac{\chi^\lambda_\alpha}{z_\alpha} \prod_i p_i^{a_i} = \sum_k \sum_{\alpha\vdash n-k} \frac{\chi^{\mu/k}_\alpha}{z_\alpha}p_\alpha $$ $$ \qquad = \sum_k s_{\mu/k}. $$ Let $s_k^\perp$ denote the linear operator taking $s_\lambda$ to $s_{\lambda/k}$. Let $\psi$ denote the linear operator taking $f$ to $\sum_k s_k^\perp f$. Let $\theta$ denote the algebra automorphism taking $p_i$ to $p_i-1$.

I claim that $\psi$ and $\theta$ are inverses (so in fact $\psi$ is an algebra automorphism). By linearity it suffices to show that $$ \psi p_\lambda = \prod_i (p_{\lambda_i}+1).\ \ \ (*) $$ Now it is not hard to see that $s_k^\perp p_\lambda$ is equal to $\sum p_\nu$, where $\nu$ is obtained from $\lambda$ by removing a set of parts (regarding equal parts as distinguishable) summing to $k$. From this (*) is immediate.

We therefore have $$ \left.\sum_k s_{\mu/k}\right|_{p_i\to p_i-1} = \theta\psi s_\mu = s_\mu, $$ as desired.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.